A língua, a história e as práticas cartoriais e religiosa em testamentos produzidos em Passos no século XIX - Rocha, Anderson Jacob (2005)
This dissertation has as a theme a study of the language, the history, and the archival and religious practices in produced wills in the city of Passos, Minas Gerais, in the nineteenth century. Our research is based on the Linguistic Historiography, which consists of a theoretical-methodological framework of research, as it proposes to explain and describe characteristics of the language and history of a community, printed in written documents. We propose, as a general objective, to examine in wills produced in Passos, in 1864, the language, the history, and the archival and religious instances in which some traces of the social memory presented in those documents are constituted. And as specific objectives, we intend to identify characteristics of the Portuguese language in use at that time and verify the juridical-religious statute of the selected wills. The relationship between language and history permits the modern man to recognize the importance of the contextual knowledge, since the historical-linguistic analysis of the document opens the reconstruction of the past of the man and his language, whereas it gives us the opportunity to understand it due to recent theories. The wills used as a sample, whose testators are João Pimenta de Abreu e Maria Joaquina do Espírito Santo, filed in the patrimony in the Memory Center Estação Cultura in Passos, MG, were analyzed on historical-linguistic approach, according to perspectives pointed by Konrad Koerner (1995,1996), among other writers and revealed marks of the Portuguese language in use at that time as well traces of archival and religious practices in that society. Under this interdisciplinary vision, essential feature of Linguistic Historiography, our research confirmed that the language can not be seen just under the look of its internal dimension, but it is necessary to look at it in the context of the atmosphere of opinion at the time that the will was elaborated. We could also realize that the will practice was common and that the Roman Catholic culture had a strong presence in the everyday life of the society in Passos in that context, considering the testators official declaration, when they declared their faith